Intraoperative tissue expansion as an alternative approach for hand syndactyly management to avoid skin grafts in children - Kravljanac, Djordje; Simic, Radoje; Milovic, Ivan (Vojnosanitetski pregled, 2020)
Background/Aim. A great number of syndactyly release techniques have been described over last two centuries. The aim of our study is outcome assessment of congenital syndactyly surgery using temporary tissue expansion of the dorsal hand and local flaps, without skin grafts. Methods. This study included children with congenital hand syndactyly treated in period from 2009–2015 by operative technique with temporary tissue expansion of the dorsal hand skin and local flaps, without skin grafting. In all cases surgery was performed under general anesthesia. According to Weber’s descriptive method, the functional outcome at the end of the follow-up period was categorized as good, fair or bad. All patients were evaluated for associated anomalies. Results. A total of 26 children (20 males, 6 females), aged from 6 months to 6 years (average age of 23 months), were operated by previously described technique. There were 20 patients with complete syndactyly and 6 with incomplete, mostly involving the third web. Associated anomalies were diagnosed in 9 patients. The follow-up period ranged from 1 to 5 years with average duration of 2.6 years. The functional results were good in 20 patients, fair in 5 and bad in 1 patient. Conclusion. Surgical procedure with temporary tissue expansion of the dorsal hand skin and local flaps, without skin grafting is effective method of congenital syndactyly treatment in children with good functional and aesthetic results. The advantages of this technique are the reduction of surgery duration and avoiding certain complications, such as web hair growth, hyperpigmentation and hypertrophic scars.